BERAT VOLUME PEREKAT GEOPOLIMER BERBAHAN DASAR ABU SABUT KELAPA - Widnyana, I Nyoman Suta; Salain, I Made Alit Karyawan; Sutarja, I Nyoman; Widiarsa, Ida Bagus Rai (Jurnal Ilmiah Teknik Sipil, 2022)
This study presents the effect of the comparison between precursors and alkaline activators on the volume weight of geopolymer binder. Geopolymer binder uses coconut fiber ash (CFA) as a precursor which contains: SiO2 (8,24%), K2O (70,6%), Cl (14,1%), P2O5 (2,3%) and Fe2O3 (2,25%). Use an alkaline activator: a solution of sodium silicate (SS) and sodium hydroxide (SH) with a molar concentration of 14M. The purpose of volume weight testing is to determine the density level of materials incorporating geopolymer binders. Variation in the proportion of the mixture of precursors (P) and alkaline activator (A) used the ratio: 70%:30%; 75%:25%; 80%:20% and the ratio between alkaline activator Na2SiO3 (SS) and NaOH solution (SH) is: 1:1; 1,5:1; 2:1 to the weight of the precursor. Specimens were printed as cubes with dimensions (50x50x50)mm and tested at specimen 7 and 28 days, respectively. The volume weight test standard refers to SNI 1973:2008. Test results show get a raise ratio of P/A and SS/SH will result in an increasing volume weight value while the volume weight value decreases by 1,3% - 1,4% along with the increase in specimen age.